The performance of MIMO system using MRT scheme in vehicular systems. (9th September 2016) - Ilhan, Haci
Summary: In this paper an inter‐vehicle multiple‐input multiple‐output system using maximal ratio transmission (MRT) scheme is proposed, and its performance is investigated where the proposed system uses multiple antennas for transmission and reception. It has the advantage of increasing effectively the diversity order without changing the receiver. As far as we know, MRT has not been employed in vehicular systems to improve system performance. Specifically, error performance of the MRT with different number of antennas at the transmitting and receiving stations has been examined, ie, MRT (2, 1) and MRT (2, 2) in a vehicular system in which cascaded Nakagami‐ m fading distribution used. First, we derive expressions of probability distribution function and then moment generating function of end‐to‐end signal‐to‐noise ratio. Based on these expressions, we obtain the symbol error rate expression on account of examining the performance of the considered system. Then, the upper bounds for the symbol error rate expressions for high enough signal‐to‐noise ratio values have been calculated. Finally, we validate the confirmation of obtained theoretical results through simulation results and furthermore show that the multiple‐input multiple‐output system using MRT scheme can provide the full diversity . Abstract : This paper presents the error rate performance of an inter‐vehicle multiple‐input multiple‐output system using maximal ratio transmission scheme by examining symbol error rate expression and diversity order of proposed system. The confirmation of obtained theoretical results is validated through simulation results, and furthermore, it is shown that the multiple‐input multiple‐output system using maximal ratio transmission scheme over cascaded Nakagami‐ m channels can provide the full diversity.